2015
DOI: 10.1523/jneurosci.0696-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Organization and Spatiotemporal Firing Patterns of Layer 3 Neurons in the Rat Medial Entorhinal Cortex

Abstract: Layer 3 of the medial entorhinal cortex is a major gateway from the neocortex to the hippocampus. Here we addressed structure-function relationships in medial entorhinal cortex layer 3 by combining anatomical analysis with juxtacellular identification of single neurons in freely behaving rats. Anatomically, layer 3 appears as a relatively homogeneous cell sheet. Dual-retrograde neuronal tracing experiments indicate a large overlap between layer 3 pyramidal populations, which project to ipsilateral hippocampus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 50 publications
(34 reference statements)
5
55
0
Order By: Relevance
“…Previous descriptions of modular distribution of histochemical markers in superficial layers of MEC of rodents include clusters of calbindin-positive cells (Fujimaru and Kosaka, 1996), zinc-positive terminals (Slomianka and Geneser, 1997) and acetylcholinesterase patches (Slomianka and Geneser, 1991), yet the interrelation of these different markers was unknown. Here we show that, in addition to the recently described calbindin-patches which overlap with AChE activity (Ray et al, 2014), the MEC contains a complementary modular system, involving dendrites of PCP4-positive L3 and L5 pyramidal cells overlapping with zinc activity ( Figure 6 ; Tang et al, 2015). Interestingly, presynaptic zinc and PCP4 seem to have overlapping or complementary distribution throughout the entire hippocampal region (Ishihara and Fukuda, 2016).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Previous descriptions of modular distribution of histochemical markers in superficial layers of MEC of rodents include clusters of calbindin-positive cells (Fujimaru and Kosaka, 1996), zinc-positive terminals (Slomianka and Geneser, 1997) and acetylcholinesterase patches (Slomianka and Geneser, 1991), yet the interrelation of these different markers was unknown. Here we show that, in addition to the recently described calbindin-patches which overlap with AChE activity (Ray et al, 2014), the MEC contains a complementary modular system, involving dendrites of PCP4-positive L3 and L5 pyramidal cells overlapping with zinc activity ( Figure 6 ; Tang et al, 2015). Interestingly, presynaptic zinc and PCP4 seem to have overlapping or complementary distribution throughout the entire hippocampal region (Ishihara and Fukuda, 2016).…”
Section: Discussionsupporting
confidence: 60%
“…The apical dendrites of PCP4-positive cells from layers 3 and 5 of MEC bundle in MEC layer 2 (Tang et al, 2015). Thus, we tested whether PCP4-positive apical dendrites co-localize with the zinc modules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have identified a substantial subset of mEC cells as nonspatial (Kropff et al, ; Latuske et al, ; Tang et al, ; Tang et al, ; Zhang et al, ). In contrast, recent work utilizing more sophisticated classification criteria found that almost all mEC cells exhibit some degree of spatial firing (Diehl et al, ; Hardcastle, Maheswaranathan, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, two layer 2 subtypes were classified as RELN + and one as CALB1 + (Witter et al, 2017). Other upper-layer subtypes were depicted based on marker gene expression of LAMA3 , PDGFD , IL1RAPL2 , and PCP4 (Ramsden et al, 2015; Tang et al, 2015; Ohara et al, 2018). The middle-to-deep layer subtypes were delineated by the specific gene expression of RORB , THEMIS , ADRA1A , and TLE4 .…”
Section: Methodsmentioning
confidence: 99%